Indigenous Standpoint Theory: ethical principles and practices for studying Sukuma people in Tanzania - Iddy, Hassan (The Australian Journal of Indigenous Education, 2020)
Abstract Indigenous Standpoint Theory (IST) is yet to be widely applied in guiding the conduct of research that involves Indigenous people in Africa. In reference to Tanzania, this approach is new. There has been no study in the context of Tanzania which has used IST, despite the presence of many Indigenous people in the country. IST is widely used in Australia, New Zealand and Canada to guide the conduct of research when studying Indigenous people. In this paper, I show how I developed nine ethical protocols for conducting culturally, respectful and safe research with the Sukuma people in Tanzania and how I used those protocols within a research project on girls and secondary education in rural Tanzania. By developing these protocols, a significant new contribution to the area of IST in Tanzania and Africa in general has been established. These protocols may serve as a starting reference point for other future researchers in Tanzania if they apply IST in their research such that the voices of Indigenous people may be heard, and the community has a greater degree of control and input in the planning and designing of the project, as well as the analysis and dissemination of the information.